Case Report: Preoperative Hormone Replacement Therapy in Hypocortisol and Hypothyroid Patients with Residual Pituitary Adenoma Tumors - Nasution, Huwainan Nisa (Universitas Muhammadiyah Sumatera Utara, 2021)
Pituitary tumors are benign tumors that occur in the pituitary gland with a presentation of 10% of all intracranial tumors. If the size of the tumor is 1 cm, the pituitary tumor is called a macroadenoma, the large size will have a mass effect so that there is an emphasis on the tumor area and its surroundings. This emphasis will manifest in hyposecretion of the hormones produced in the pituitary. We report a case of 57-year-old male with complaints of decreased vision since 3.5 months. The patient had previously been diagnosed with a pituitary tumor 6 years ago and had surgery. After diagnostic steps, the patient is diagnosed with a residual pituitary adenoma tumor with hypocortisol and hypothyroidism. Hormone replacement therapy was performed by administering methilprednisolone tablets 16 mg-0-8 mg and levothyroxine tablets 1 x 50 g. The patient was planned to undergo an Endoscopic Endonasal Excision Tumor surgery with 125 mg/12 hour preoperative injection of methilprednisolon. The provision of preoperative hormone replacement therapy aims to correct hormonal imbalances that can be an intraoperative complication